Pengaruh Rasio Keuangan, Ukuran Perusahaan, dan Umur Perusahaan terhadap Tax Avoidance - Fanny Sterling; Silvy Christina (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This study aims to obtain empirical evidence regarding the effect of financial ratios, company size and company age on tax avoidance. There are several factors used by the company in this study, namely profitability, leverage, company size, sales growth, company age and capital intensity to tax avoidance. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2017 to 2019. Determination of the sample in this study using purposive sampling method, in which resulting 178 data are taken as sample. The data in this study were analyzed using multiple regression methods. The results of this study indicate that the profitability variable has a positive effect on tax avoidance while leverage has a negative effect on tax avoidance. The variables of company size, sales growth, company age and capital intensity have no effect on tax avoidance.